Malawi : Fourth and Fifth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waivers of Nonobservance of Performance Criteria-Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report ;, 2008)
Progress on fiscal policy during 2006/07 in Malawi was slower than expected. The 2006/07 (July-June) fiscal strategy focused on reducing domestic debt. In the third Poverty Reduction and Growth Facility (PRGF) review, the end-June target for domestic debt repayments was increased substantially. Domestic borrowing exceeded the adjusted target at end-December 2006 by MK 4.1 billion (0.9 percent of GDP). The government partially redressed this overrun by curtailing discretionary spending in the fourth quarter, as the scale of the end-December overrun became clear.